Design and Development of a Digital Management Information System to Support Institutional Branding and Public Relations Services - Khairul Anwar hafizd; Rina Pebriana; M. Zainal Akli (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2026)
Digital transformation is driving universities to optimize the use of information technology not only in the delivery of academic services but also in strengthening institutional branding and improving the quality of Public Relations (PR) services. The implementation of the Smart Campus concept has become one strategy for integrating various digital services, including institutional information management and PR services. This study aims to develop a Smart Branding and PR Services Information System capable of integrating institutional information management and PR services into a single centralized digital platform. The developed system facilitates the management of institutional profile and department information, as well as the digitization of PR services, such as graphic design requests, event coverage, social media posts, and passport photo production. In addition to serving as an official information channel accessible to the public, this system also supports a more structured, documented, and integrated public relations service process. The system’s implementation demonstrates that institutional information management has become more centralized, public relations service processes are more efficient, and it supports improved effectiveness in information dissemination and the strengthening of the institution’s image. Thus, the developed information system can serve as a solution to support the implementation of Smart Campus through integrated information management and public relations services, thereby enhancing the effectiveness of institutional branding in the era of digital transformation.